(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Research background: Globalization, the impact of geopolitical conditions, the rapid rise of inflation, and the rapidly changing conditions intensifies competition between companies, which influence companies think about expanding their services. Economic survival forces companies to think about reorganizations through mergers and acquisitions. Companies consider mergers and acquisitions as a strategy for product market expansion to improve competitive advantage, however, achieving the expected success through mergers and acquisitions poses serious challenges to company management and does not provide the expected value from these transactions. Acquisitions and mergers without reorganization business management model may not deliver the expected benefits.; Purpose of the article: to present a reorganisation business model to enable Latvian Real estate service companies to implement the product market expansion strategy through acquisitions and mergers and reorganisation processes. Methods: A monographic and descriptive method was used to analyse the theoretical aspects of company strategies, secondary data analysis and expert interview were used to describe the situation of real estate management service industry, but quantitative research method such as analysing of statistical data of the apartment maintenance companies, in connection with the comparative, analytical, deductive, logical approach method was used in this research. Findings & Value added: Real estate management companies in Latvia face the conditions created due to the influence of globalization and geopolitical conditions - market limitations to expand. Companies, their managers have not enough knowledge of reorganization process, and many other factors about properly conducted reorganization transactions, incl. about acquisitions, due diligence, transaction progress, therefore companies need a reorganization business management model suitable for reorganization transactions.